2020
DOI: 10.9734/ijecc/2020/v10i1130270
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Farming on Sustainable Agriculture System and Marketing Potential: A Review

Abstract: Organic farming helps to improve the health of agro-ecosystem by its holistic approach using on-farm agronomic, biological and mechanical methods in exclusion of all synthetic off-farm inputs. Although the organic farming is eco-friendly, question arises about possibility to adopt the organic farming for the large scale and its impacts on maintaining the productivity of land to meet the food security challenges from the ever-increasing population of the world. But at the same time, consumer’s behaviour and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…Traditional farming practitioners are facing some problems such as biomass and residue burning, bare and long fallow phase, injudicious cultivation, mining of soil fertility, careless cropping and irrigation practices [50]. These problems can be overcome by following recommended management practices such as conservation tillage, cover and nurse cropping, crop rotation, integrating climate resilient trees and crops with livestock, efficient cropping and irrigation practices, mulching, proper use of resources and sensible use of off-farm inputs [50]. Some studies compared the adaptation and benefits of these two forms of AF practices [50,51].…”
Section: Amalgamation Of Traditional and Improved Af Practices To Enh...mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional farming practitioners are facing some problems such as biomass and residue burning, bare and long fallow phase, injudicious cultivation, mining of soil fertility, careless cropping and irrigation practices [50]. These problems can be overcome by following recommended management practices such as conservation tillage, cover and nurse cropping, crop rotation, integrating climate resilient trees and crops with livestock, efficient cropping and irrigation practices, mulching, proper use of resources and sensible use of off-farm inputs [50]. Some studies compared the adaptation and benefits of these two forms of AF practices [50,51].…”
Section: Amalgamation Of Traditional and Improved Af Practices To Enh...mentioning
confidence: 99%
“…These problems can be overcome by following recommended management practices such as conservation tillage, cover and nurse cropping, crop rotation, integrating climate resilient trees and crops with livestock, efficient cropping and irrigation practices, mulching, proper use of resources and sensible use of off-farm inputs [50]. Some studies compared the adaptation and benefits of these two forms of AF practices [50,51]. Studies reported nearly threefold increase in annual income and diverse benefits from improved AF practices as compared to traditional AF practices [51].…”
Section: Amalgamation Of Traditional and Improved Af Practices To Enh...mentioning
confidence: 99%
“…Organic agriculture avoids the use of synthetic inputs and is based mainly on crop rotations, the use of animal manure (e.g., chicken manure, bovine manure, etc.) and crop residues as soil improvement and nutrient-mobilizing and plantprotecting biological systems (Patle et al, 2020).…”
Section: Modelos De Producción Agroalimentaria Para La Nutrición Y La Saludmentioning
confidence: 99%
“…The purpose is to position agriculture within a holistic context and recover its humanistic condition (Horrigan et al, 2002). However, it is worth acknowledging de nutrientes y protección de plantas (Patle et al, 2020).…”
Section: Modelos De Producción Agroalimentaria Para La Nutrición Y La Saludmentioning
confidence: 99%
“…For instance, in Mexico, the milpa system with the simultaneous planting of different varieties of native corn in association with other crops, the practices of minimum tillage, and the zero presence of agrochemicals, have maintained a very high diversity of animals, plants, and microorganisms in the soil of the ecosystem (Rocha and Gastélum, 2020); which allows the soil associated with maize to present a dynamic microbial diversity on short-term scales (Rebollar et al, 2017). The ecological farming system avoids the usage of synthetic supplies and is principally based on crop rotation and incorporation of crop residues, fertilizers of animal origin, organic farm waste, and biological systems of nutrient cycling and plant protection, increasing nutrient and antioxidant content in crops (Patle et al, 2020;Petkova et al, 2020). This system considers plants as part of a complete system within nature and is based on the improvement of biological diversity in the field to alter the habitat of pests and Based on high inputs of agrochemicals which alter the microbiota associated with the plan.…”
Section: Sustainable Nutrition-sensitive Agriculture For Human Healthmentioning
confidence: 99%